Hybrid formulations of liposomes and bioadhesive polymers improve the hypotensive effect of the melatonin analogue 5-MCA-NAT in rabbit eyes. - Daniela Quinteros (Public Library of Science (PLoS), 2014)
For the treatment of chronic ocular diseases such as glaucoma, continuous instillations of eye drops are needed. However, frequent administrations of hypotensive topical formulations can produce adverse ocular surface effects due to the active substance or other components of the formulation, such as preservatives or other excipients. Thus the development of unpreserved formulations that are well tolerated after frequent instillations is an important challenge to improve ophthalmic chronic topical therapies. Furthermore, several components can improve the properties of the formulation in terms of efficacy. In order to achieve the mentioned objectives, we have developed formulations of liposomes (150-200 nm) containing components similar to those in the tear film and loaded with the hypotensive melatonin analog 5-methoxycarbonylamino-N-acetyltryptamine (5-MCA-NAT, 100 µM). These formulations were combined with mucoadhesive (sodium hyaluronate or carboxymethylcellulose) or amphiphilic block thermosensitive (poloxamer) polymers to prolong the hypotensive efficacy of the drug. In rabbit eyes, the decrease of intraocular pressure with 5-MCA-NAT-loaded liposomes that were dispersed with 0.2% sodium hyaluronate, 39.1±2.2%, was remarkably higher compared to other liposomes formulated without or with other bioadhesive polymers, and the effect lasted more than 8 hours. According to the results obtained in the present work, these technological strategies could provide an improved modality for delivering therapeutic agents in patients with glaucoma.